TEACHER’S PERCEPTION ABOUT THE SCHOOL PERFORMANCE OF ROMA STUDENTS - Norbert Tóth (Különleges Bánásmód, 2024)
The current paper aims to shed light on the problem of Roma students' school performance through the perception of teachers. We examine the phenomenon at the level of locality, relying on qualitative research methodology. The empirical data collection was carried out at the István Király Baptist Primary School in Kótaj, in the county of Szabolcs-Szatmár-Bereg, during which semi-structured interviews were recorded (N=15).